Molecular Docking and Pharmacokinetic Parameters of Moringa Chemical Compounds with Folate Receptor - Hasan, Rahmawaty; Bahi, Rizky Resvita (Proceeding International Conference on Religion, Science and Education, 2025)
Folic acid is a micronutrient that is needed by pregnant women in the development of the nervous system. Consumption of Moringa leaves can increase hemoglobin levels, >11 g%. Potential nutrients contained in Moringa leaves can meet the nutritional needs of pregnant women. However, the chemical compound interact with target of the molecular action of folic acid is not known. This study aims to identify the chemical compound of Moringa leaves that can interact with folate receptors in silico and predict pharmacokinetic parameters based on the SwissADME webserver. The selected molecular target is the alpha-folate receptor (PDB: 4LRH) with a molecular docking technique using Autodock 4.2 which has been previously validated to the native ligand. The results of molecular docking showed that the potential compounds of Moringa leaves were glucosinalbin, niazidin, niazinin, niazirin and rhamnetin which had an energy value of less than -8 kcal/mol. However, the potential of these compounds is not more than the energy value of folic acid as a native ligand on a folic acid receptor macromolecule. Prediction results of pharmacokinetic parameters showed that all potential compounds of Moringa leaf showed that niazinin, niazirin, and rhamnetin were highly absorbed in the gastrointestinal tract, except for niazidin and glucosine. Rhamnetin is a potential compound that can be catalyzed by CYP3A4, CYP1A2 and CYP2D6 enzymes.